Additive Interaction Between Onabotulinumtoxin-A and Erenumab in Patients With Refractory Migraine - Silvestro, Marcello; Tessitore, Alessandro; Scotto di Clemente, Fabrizio; Battista, Giorgia; Tedeschi, Gioacchino; Russo, Antonio (Frontiers in Neurology, 2021)
In the last decade, notable progresses have been observed in chronic migraine preventive treatments. According to the European Headache Federation and national provisions, onabotulinumtoxin-A (BTX-A) and monoclonal antibodies acting on the pathway of calcitonin gene–related peptide (CGRP-mAbs) should not be administered in combination due to supposed superimposable mechanism of action and high costs. On the other hand, preclinical observations demonstrated that these therapeutic classes, although operating directly or indirectly on the CGRP pathway, act on different fibers. Specifically, the CGRP-mAbs prevent the activation of the Aδ-fibers, whereas BTX-A acts on C-fibers. Therefore, it can be argued that a combined therapy may provide an additive or synergistic effect on the trigeminal nociceptive pathway. In the present study, we report a case series of 10 patients with chronic migraine who experienced significant benefits with the combination of both erenumab and BTX-A compared to each therapeutic strategy alone. A reduction in frequency and intensity of headache attacks (although not statistically significant probably due to the low sample size) was observed in migraine patients treated with a combined therapy with BTX-A and erenumab compared to both BTX-A and erenumab alone. Moreover, the combined therapy with BTX-A and erenumab resulted in a statistically significant reduction in the symptomatic drug intake and in migraine-related disability probably related to a reduced necessity or also to a better responsiveness to rescue treatments. Present data suggest a remodulation of current provisions depriving patients of an effective therapeutic strategy in peculiar migraine endophenotypes.